Steroid-Dependent Nephrotic Syndrome in a Pediatric Patient With Type-1 Diabetes Mellitus - Nisha S. Singh; Aubree Crabb; Ikuyo Yamaguchi (Case Reports in Nephrology)
Proteinuria in a patient with long-standing Type 1 diabetes mellitus (T1DM) usually suggests diabetic kidney disease (DKD). However, DKD occurs late in the disease and is associated with hypertension and retinopathy. We report an adolescent with T1DM who, 1 year after initial diagnosis, developed nephrotic syndrome (NS). He was treated with steroids but developed frequent relapses and became steroid-dependent. A subsequent kidney biopsy revealed minimal change disease (MCD) and mild DKD. He was treated with mycophenolate mofetil (MMF) and remains in remission. Primary podocytopathy, such as MCD, is a rare cause of NS in a patient with T1DM. Indications for kidney biopsy and treatment options are similar to those of other children with a diagnosis of NS. This report highlights that, although rare, primary glomerulopathy can occur in pediatric diabetic patients and should be considered in the differential diagnosis of proteinuria, as early recognition and intervention can lead to favorable outcomes.